Disseminação seletiva da informação no contexto das organizações aprendentes: proposta de um modelo digital integrado ao SIGAA na Universidade Federal do Rio Grande do Norte - Amaral, Marjorie Rosielle Silva do (2014)
It presents the peculiarities of selective dissemination of information, such service contributes to sharing personalized informational content, considering the importance of information, seen as a key element in modern society that inspires and challenges its management. Its main goals were investigate the construction the model of Selective Dissemination Information integrated to SIGAA at UFRN by making an effort for professors to have current, relevant information at his or her service so they can strengthen the construction process of knowledge from the individuals that demand such things. The time frame done in the development literature of this search was between 1978 and 2014, therefore from its conceptual apprehension, it allows better understanding of the dissemination process of information for effective capability of the proposed action. For that, the research assumed a qualitative approach being classified as an explorative type and it was done through the methodological strategy of action research. Interviews were held with the Head of the Library System and the superintendent of information from UFRN, with the intent of collecting information and creating partnerships to the development of service. The faculty coordinators from basic research of Centro de Ensino Superior de Serido (CERES)/UFRN were questioned to identify if these individuals felt difficulties in finding information material about their area of research and if they considered the service relevant to the institution. In regards to the results, the research revealed that the majority of the professors felt some difficulty in finding the articles as well as the essays and/or thesis and they classify the designing of the service as extremely relevant to UFRN. Thus, this action research permitted the engaging construction of three beginning steps of the fundamental service in Souto (2010), which were: the achievement of the proposed diagnosis in the information dissemination in the UFRN scope, the politics definition of service and the achievement of organization planning in the SIGAA service.